Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3310/hsdr07260
|View full text |Cite
|
Sign up to set email alerts
|

Sense-making strategies and help-seeking behaviours associated with urgent care services: a mixed-methods study

Abstract: BackgroundPolicy has been focused on reducing unnecessary emergency department attendances by providing more responsive urgent care services and guiding patients to ‘the right place’. The variety of services has created a complex urgent care landscape for people to access and navigate.ObjectivesTo describe how the public, providers and policy-makers define and make sense of urgent care; to explain how sense-making influences patients’ strategies and choices; to analyse patient ‘work’ in understanding, navigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 180 publications
2
19
0
Order By: Relevance
“…Additionally, those aged 18‐44 were more likely to feel overwhelmed when they had an unexpected health problem 24 . These data echo Turnbull et al's findings that young adults more frequently identified themselves as anxious and prone to worrying about their health and linked this to their use of urgent and emergency services 22 . This anxiety and lack of confidence may be an age effect: young adults may be facing unfamiliar symptoms for the first time and be less confident in making independent decisions about their seriousness, and have less familiarity with services.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Additionally, those aged 18‐44 were more likely to feel overwhelmed when they had an unexpected health problem 24 . These data echo Turnbull et al's findings that young adults more frequently identified themselves as anxious and prone to worrying about their health and linked this to their use of urgent and emergency services 22 . This anxiety and lack of confidence may be an age effect: young adults may be facing unfamiliar symptoms for the first time and be less confident in making independent decisions about their seriousness, and have less familiarity with services.…”
Section: Discussionsupporting
confidence: 69%
“…Media portrayals often depict young adults as being used to a 24/7 culture and expecting services to be immediately available, or using EDs due to their chaotic lifestyles 19,20 . In research, a recent study exploring use of a range of urgent care services (111, ED, minor injuries unit, urgent care centre) found young adults identified the lack of alternatives as their reason for using EDs 21,22 . This could be driven by lack of access to GP services, 20,23 lack of knowledge of alternatives or confusion about how to use them 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…On the demand side, public health campaigns admonish patients via marketing campaigns with blunt messages such as Don’t go to A&E . However, in a chronically under-resourced system, making relatively minor adjustments will yield relatively small results [ 13 ], and applying a broad approach to dissuading use of medical resources may have unintended negative consequences; most people cannot adequately distinguish between problems that are urgent , emergency , and routine care [ 15 ]. While there is much excitement about the potential for video consultations and the UK National Health Service (NHS) GP contract even states “every patient will have the right to online and video consultation by April 2021,” the accumulated experience has been that health IT solutions within the NHS tend to suffer “non adoption, abandonment, and challenges to scale-up, spread, and sustainability” [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These differences challenge the successful implementation of solutions. Variation in demographic profiles, community healthcare needs and service availability influence how and when people access services, including the decision to present to an ED with a 'nonurgent' condition [15]. Socioeconomic position, for example, has been identified as having both a positive and negative correlation with populations accessing EDs.…”
Section: Introductionmentioning
confidence: 99%